Inference of genetic networks using multi-objective hybrid SPEA2+ from microarray data - Showkat, Dilruba; Kabir, Mitra Lutful (© 2013 IEEE, 2016)
This conference paper was presented in the 12th IEEE International Conference on Cognitive Informatics and Cognitive Computing, ICCI*CC 2013; New York, NY; United States; 16 July 2013 through 18 July 2013 [© 2013 IEEE] The conference paper's definite version is available at: http://dx.doi.org/10.1109/ICCI-CC.2013.6622244